ANALISA KINERJA TURBIN TURGO DAN TURBIN PELTON SKALA LABORATORIUM - Ramaputra, Dharmacakra; Haurissa, Jusuf (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2022)
This study aims to analyze the performance comparison of turgo turbines and laboratory-scale Pelton turbines. The research was conducted using the H41D/C turbine simulator in the Mechanical Engineering Laboratory of Jayapura University of Science and Technology. Turgo turbines and Pelton turbines were installed in the turbine simulator alternately, and then the turbines were tested for comparison of power and efficiency. During the testing process, the data is measured by turbine rotation, flow rate, and flow pressure using the ADC, then the results are entered into the table, then processed to produce graphs for analysis. From the results of the study, it was concluded that from a comparative analysis of the performance of turgo and Pelton turbines based on a comparative analysis of the power and efficiency of the largest turgo and Pelton turbines at each nozzle opening of 25%, 50%, 75% and 100%, turgo and Pelton turbines with nozzle openings 25% of the power generated by the turgo turbine is 67.96 W. The efficiency is 35.49, while the energy in the Pelton turbine is 83.72W. The efficiency is 41.71, at the nozzle opening, 50% of the power and efficiency of the turgo and Pelton turbines are the largest, the power of the turgo turbine is 87, 37W and 44.75% efficiency. In comparison, the Pelton turbine power is 95.5W and 46.66% efficiency. At a nozzle opening of 75%, the greatest strength and efficiency of the turgo and Pelton turbines, the power and efficiency generated in the turgo turbine is 87.18W, and the efficiency is 45.09. In contrast, in the Pelton turbine, the energy produced is 94.86W, and the efficiency is 49.06%. At 100% nozzle opening power and the highest efficiency of the turgo and Pelton turbines, the turgo turbine has a strength of 86.62W and an efficiency of 44.96%. In comparison, the Pelton turbine produces 97.5W of energy and an efficiency of 50.38%.